Predictors for Celiac Disease in Adult Cases of Duodenal Intraepithelial Lymphocytosis. Issue 6 (July 2015) - Aziz, Imran; Key, Tim; Goodwin, John G.; Sanders, David S.
Abstract : Background: Duodenal intraepithelial lymphocytosis (D-IEL) is an early marker for celiac disease (CD). However, the majority of cases are due to non-CD–related conditions. Goals: To identify the predictors of CD when presented with D-IEL. Methods: A total of 215 adult patients with D-IEL had undergone prospective and systematic evaluation for CD and other recognized associations. The gold-standard diagnosis of CD was based upon the presence of HLA-DQ2 and/or DQ8, persistence or progression of D-IEL following a gluten challenge, followed by symptomatic improvement on a gluten-free diet. Binary logistic regression models, adjusting for age and sex, were subsequently performed to compare presenting variables between CD and non-CD cases, and to determine their sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV). Results: CD was diagnosed in 48 cases (22%) and non-CD in 167 cases (78%). There was no statistical difference in baseline demographics, clinical symptoms (ie, diarrhea, weight loss, abdominal pain), anemia, or hematinics between the CD and non-CD group. Patients with CD, in comparison with non-CD, were significantly more likely to have a positive family history of CD (21% vs. 3.6%, OR 6.73; PPV 62.5%, NPV 81%, specificity 96.4%), positive HLA-DQ status (100% vs. 49.1%; PPV 36.4%, NPV 100%, specificity 50.9%), and presence of endomysial antibody (EMA) (48% vs. 0%; PPV 100%, NPV 87%, specificity 100%); all P ⩽0.001. A normal tissue transglutaminase antibody (TTG) level was seen in 29.2% CD and 83.2% non-CD cases (OR 0.084, P <0.001; PPV 9.2%). There was no difference in the prevalence of TTG levels 1 to 2×upper limit of normal (ULN) between the groups (29.2% CD vs. 14.4% non-CD; PPV 33% to 38%). However, TTG levels between 3 and 20×ULN were significantly more prevalent in the CD group (33.3% vs. 2.4%, PPV 66.6% to 89%), whereas a TTG>20×ULN was exclusive to CD (8.3%, P <0.001, PPV 100%). Conclusions: In the setting of D-IEL, only the presence of a positive EMA or TTG>20×ULN at the outset can be used to make an immediate diagnosis of CD. Gastrointestinal symptoms, family history, anemia, or other celiac serology results do not reliably distinguish CD from non-CD without further investigations.